2009
DOI: 10.1364/oe.17.007088
|View full text |Cite
|
Sign up to set email alerts
|

Polarizer-free, electrically switchable and optically rewritable displays based on dye-doped polymer-dispersed liquid crystals

Abstract: This work demonstrates the feasibility of a polarizer-free, electrically switchable and optically rewritable display based on dye-doped polymer-dispersed liquid crystals (DD-PDLCs). Experimental results indicate that the doped dyes are homeotropically adsorbed onto the polymer film when an appropriate AC voltage is applied during patterning. The adsorbed dyes in the illuminated region then align the liquid crystals homeotropically, and produce a transparent pattern in the scattering background without any pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…The photoalignment technique ensures that LCs are typically aligned on a substrate by irradiating the surface that contains photoreactive molecules with a linearly polarised light (visible or ultraviolet light). Over the past decades, the experimental results of anchoring transition caused by several external factors, such as temperature, [11] electric field [12] and photoisomerisation, [7,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The photoalignment technique ensures that LCs are typically aligned on a substrate by irradiating the surface that contains photoreactive molecules with a linearly polarised light (visible or ultraviolet light). Over the past decades, the experimental results of anchoring transition caused by several external factors, such as temperature, [11] electric field [12] and photoisomerisation, [7,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these materials induces a distinct phenomenon. Several azo dyes, either embedded into the polymer film, [3,7,13] or dissolved in LC mixtures, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] exhibit effective anchoring transition via illumination with polarised light. One of the effects of photoalignment involves the light-induced reorientation of the azobenzene chromophore, which is promoted by trans-cis isomerisation cycles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jau et al demonstrated a photo-rewritable transmissive flexible-LCD that was based on the aligning effect of the photo-induced adsorption of azo dye on a flexible indium zinc oxide/polycarbonate (IZO/PC) substrate. A polarizer-free, electrically switchable and optically rewritable display that is based on dye-doped polymer-dispersed LCs has been developed [51]. Owing to bulkmediated alignment, the adsorbed dye in the illuminated region aligns the LC homeotropically and thereby generates a transparent pattern on the scattering film without any polarizer.…”
Section: Bulk-mediated Photo-isomerization and Adsorption Effectsmentioning
confidence: 99%
“…anchoring effect that increases driving voltages, indicating that the operated voltage of a traditional PDLC scattering mode light shutter is high [6,7]. Accordingly, many scientists have recently paid much attention to such approaches as surface rubbing effect [8], dichoric dyes [9], and others, to reduce the operated voltage of PDLCs.…”
mentioning
confidence: 99%